Comparison of the structure–function relationship between compass microperimetry and Humphrey field analyser in myopic open-angle glaucoma eyes. Issue 4 (8th December 2020) - Shin, Joong Won; Song, Min Kyung; Won, Hun Jae; Jo, Younhye; Kook, Michael S
Abstract : Background/aims: To compare the structure–function relationship between compass microperimetry (CMP; CenterVue, Padova, Italy) and Humphrey field analyser (HFA; Carl Zeiss Meditec, Dublin, California, USA) in open-angle glaucoma (OAG) eyes with myopia. Methods: Circumpapillary retinal nerve fibre layer thickness (cpRNFLT) and visual field (VF) mean sensitivity (MS) were obtained in 90 OAG subjects using the optical coherence tomography, CMP and HFA in a random order. The global and sectoral structure–function relationships between the cpRNFLT and VFMS were assessed with different VF devices (CMP vs HHA) in OAG eyes with and without myopia. Results: Overall, the global and regional structure–function relationships between the two devices did not show significant differences except for the superotemporal sector. In the myopic subgroup, the global association between the average cpRNFLT and VFMSCMP was significantly stronger than that between the average cpRNFLT and VFMSHFA (r=0.806 vs. 0.720, p=0.035). The presence of myopia and higher global cpRNFLT were significantly associated with the greater global VFMS differences between the two devices (p<0.05). Conclusion: In general, structure–function relationship is similar between CMP and HFA in OAG eyes. However, the global structure–function relationship is significantly stronger with CMP than with HFA in OAG eyes with myopia.